The relationship between virulence and drug resistance genes in Pseudomonas aeruginosa and antibiotic resistance: a targeted next-generation sequencing approach - Wei, Huanhuan; Fu, Yuanyong; Qin, Weijuan; Liang, Zhengyi; Zhou, Liyan; Gao, Jingwei; He, Shiyi; Wu, Xiaoning (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivePseudomonas aeruginosa is an opportunistic pathogen responsible for nosocomial infections in critically ill and immunocompromised patients. To elucidate genomic-phenotypic-clinical correlations in P. aeruginosa infections, this study integrates targeted next-generation sequencing (tNGS) with conventional diagnostics.MethodsA retrospective study was conducted between September, 2023 and December, 2024 at The Second Affiliated Hospital of Guangxi Medical University on patient specimens that were subjected to both conventional culture and tNGS testing. Only a single Gram-negative bacterium, P. aeruginosa, was detected by tNGS, and these isolates were subsequently analyzed in order to compare their genomic profiling (virulence/resistance genes), antimicrobial susceptibility testing (AST), and clinical characteristics.ResultsA total of 105 samples were included in the study. Exoenzyme Y gene (exoY) and O-antigen polymerase gene (wzy) were detected in 77.1% and 12.4% of the samples, respectively. Meanwhile, aminoglycoside acetyltransferase gene (aac(6’)aac(3’)), aminoglycoside resistance methyltransferase gene (armA), and chloram phenicol resistance genes (cmlA) were detected in 6.7%, 4.8%, and 12.4% of the samples, respectively. P. aeruginosa isolates detected the exoY gene exhibit a higher level of drug resistance, particularly to cefepime (32.1% vs 4.2%, p<0.05) and piperacillin-tazobactam (33.3% vs 8.3%, p<0.05). aac(6’)aac(3’) and armA genes were statistically associated with tobramycin resistance (p<0.05). The use of antibiotics before hospitalization (within 90 days), hospital-acquired infections, ICU admission, as well as pre-P. aeruginosa detection interventions including invasive procedures, catheterization, mechanical ventilation, duration of antibiotic use time≥14 days, and antibiotic use type ≥3 types (p<0.05) is associated with multidrug-resistant (MDR) and carbapenem-resistant P. aeruginosa (CRPA) infections (p<0.05). Furthermore, the detection of MDR and CRPA strains appears to lead to an increase in the duration and variety of antibiotic use, as well as prolonged of hospital stay (p<0.05).ConclusionOur study highlights the importance of integrating tNGS results, which provide insights into pathogen identification, resistance, and virulence genes, with phenotypic and clinical data in order to enhance the accuracy of diagnosis and guide treatment strategies.